Hubungan antara Self-Efficacy dan Lingkungan Kerja terhadap Kepuasan Kerja di PT. BPRS Amanah Ummah Kantor Pusat - Dewi, Effry Yani; Syahyuni, Dedy (ProBisnis : Jurnal Manajemen, 2025)
Self-Efficacy and work environment are very important factors in increasing employee job satisfaction, including at PT. BPRS Amanah Ummah. This study aims to determine the correlation/relationship of self-efficacy and work environment variables to job satisfaction variables at PT. BPRS Amanah Ummah Head Office. This study is a descriptive quantitative study that utilizes a Google Forms questionnaire distributed to all employees to collect data. The population in this study was 55 employees of PT. BPRS Amanah Ummah. The method used in this study is non-probability with a sample collection technique using a saturated sampling technique. Data processing used in this study is multiple linear regression testing and path analysis by conducting data quality testing first. The test results indicate that the data used is valid. The test results show that partially there is a significant influence between the self-efficacy and work environment variables on job satisfaction. The simultaneous determination coefficient value is 0.794 which explains that self-efficacy and work environment have an influence of 79.4% on the job satisfaction variable. It is hoped that future researchers can develop this research with a larger scope.